Reconfigurable instruments for experiments in physics - the speed of sound measurement - Thang, Trinh Vinh; Thang, Nguyen Duc; Dinh, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics, 2010)
Abstract